Composting of Garden Waste using Indigenous Microorganisms (IMO) as Organic Additive - Khalib, Siti Noor Baya; Zakarya, Irnis Azura; Tengku Izhar, Tengku Nuraiti (International Journal of Integrated Engineering, 2019)
Garden waste (GW) is considered as one of the types of municipal solid waste because of its biodegradable organic fraction.  To avoid the disposal of green waste by open burning, incineration and landfill site, it can be manage by composting process.  The objective of this study was to evaluate the performance of composting garden waste (dry leaves) by using indigenous microorganisms in term of the compost quality (pH, temperature, moisture content, C:N ratio and nutrient content). The compost has been prepared from three different mixtures of food waste for 30 days. IMO used as an organic additive during composting were prepared according to the method from previous study. The preparation of IMO consists of several phases include phase I until V with a mixture of various materials for each phase. During the composting process, all the parameters of IMO-compost obtained in a range like; pH value 8-9, temperature 30-48°C, moisture content 36-65%, nitrogen 2- 7%, phosphorus 4-8%, potassium 12-18% and C:N ratio 6-12.  The result showed that all compost quality for IMO-compost obtained in an acceptable range for final compost to establish.